2011
DOI: 10.1021/jo201119e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrazoles via Electrophilic Cyclization

Abstract: Electrophilic cyclizations of α,β-alkynic hydrazones by molecular iodine were investigated for the synthesis of 4-iodopyrazoles. α,β-Alkynic hydrazones were readily prepared by the reactions of hydrazines with propargyl aldehydes and ketones. When treated with molecular iodine in the presence of sodium bicarbonate, α,β-alkynic hydrazones underwent electrophilic cyclization to afford 4-iodopyrazoles in good to high yields. Iodocyclization was general for a wide range of α,β-alkynic hydrazones and tolerated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(59 citation statements)
references
References 148 publications
2
57
0
Order By: Relevance
“…We first prepared the required 4‐iodopyrazoles 5 and 6 from the corresponding propargyl aldehydes 1 and 2 according to our previous study as shown in Scheme . The neat reaction of ferrocenylpropargyl aldehyde ( 1 ) with phenylhydrazine at 80 °C afforded Z and E isomers of hydrazone 3 in 54 and 36% yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We first prepared the required 4‐iodopyrazoles 5 and 6 from the corresponding propargyl aldehydes 1 and 2 according to our previous study as shown in Scheme . The neat reaction of ferrocenylpropargyl aldehyde ( 1 ) with phenylhydrazine at 80 °C afforded Z and E isomers of hydrazone 3 in 54 and 36% yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…When reacted with molecular iodine, Z and E isomers of hydrazone 3 afforded ferrocenyl‐substituted 4‐iodopyrazole 5 in 90 and 92% yields, respectively. Iodocyclization of Z isomer of hydrazone 4 produced phenyl‐substituted 4‐iodopyrazole 6 in 80% yield (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…84 Electrophilic cyclizations of a,b-alkynic hydrazones by molecular iodine afford synthesis of 4-iodopyrazoles in good to high yields (Scheme 78). 85 Wu and coworkers have described a highly efficient electrophilic cyclization of N 0 -(2-alkynylbenzylidene)-hydrazide with I 2 , Br 2 , or ICl in DCM at room temperature. It provides an efficient method to construct functionalized isoquinolinium-2-yl amides (Scheme 79).…”
Section: 2 Cyclization Involving Alkynesmentioning
confidence: 99%